Patch test standard series recommended by the Brazilian Contact Dermatitis Study Group during the 2006-2011 period - Ida Alzira Gomes Duarte; Greta Merie Tanaka; Nathalie Mie Suzuki; Rosana Lazzarini; Andressa Sato de Aquino Lopes; Beatrice Mussio Fornazier Volpini; Paulo Carrara de Castro (Sociedade Brasileira de Dermatologia, 2013)
A retrospective study was carried out between 2006-2011. Six hundred and eighteen patients with suspected allergic contact dermatitis underwent the standard patch test series recommended by the Brazilian Contact Dermatitis Research Group. The aim of our study was to evaluate the variation of positive patch-test results from standard series year by year. The most frequently positive allergens were: nickel sulfate, thimerosal and potassium bichromate. Decrease of positive patch-test results over the years was statistically significant for: lanolin (p=0.01), neomycin (p=0.01) and anthraquinone (p=0.04). A follow-up study should be useful in determining which allergens could be excluded from standard series, as they may represent low sensitization risk.